Case Report: Baricitinib as an Alternative in the Maintenance Therapy for Macrophage Activation Syndrome Secondary to Nodular Panniculitis - Yi, Guanqun; Huang, Zhengping; Huang, Zhixiang; Wang, Yunqing; Deng, Weiming; Zheng, Shaoling; Li, Tianwang (Frontiers in Immunology, 2022)
Background: Macrophage activation syndrome (MAS) is a severe complication of autoimmune diseases with high mortality. We report the effectiveness of baricitinib as an option for the maintenance therapy in MAS secondary to nodular panniculitis. Case summary: A 24-year-old female patient came to our hospital with repeated fever and a skin nodule on right tibial tuberosity. Results were notable for raised serum ferritin (SF), triglycerides (TG), elevated liver function enzymes, interleukin-6 (IL-6), interferon-γ (IFN-γ), soluble interleukin-2 receptor (sIL-2R) and decreased activity of NK cells. The pathological biopsy of the subcutaneous nodules indicated nodular panniculitis. Hemophagocytic cells were found in bone marrow aspiration. She was diagnosed as MAS secondary to nodular panniculitis. With the treatment of methylprednisolone (MP) and immunoglobulin, her symptoms and laboratory data gradually improved. Nevertheless, her disease relapsed when the MP dose was tapered. Given some reports regarding the usage of JAK inhibitors in MAS, we used baricitinib (JAK1/2 inhibitor) to treat MAS and her symptom and abnormal laboratory findings returned to normal. During follow-up, though the MP dose is tapered, she is stable without a MAS recurrence. Conclusion: The case report suggested baricitinib is an option for MAS in the maintenance therapy phase and is potentially beneficial to prevent recurrence.